Simultaneous versus staged resection for synchronous colorectal liver metastases: A population-based cost analysis in Ontario, Canada - Health economic evaluation. (June 2020) - Wang, Julian; Griffiths, Christopher; Simunovic, Marko; Parpia, Sameer; Gu, Chu-Shu; Gafni, Amiram; Ruo, Leyo; Hallet, Julie; Bogach, Jessica; Serrano, Pablo E.
Abstract: Background: Simultaneous compared to staged resection of synchronous colorectal cancer liver metastases is considered safe. We aimed to determine their cost implications. Study Design: Population-based cohort was generated by linking administrative healthcare datasets in Ontario, Canada (2006–2014). Resection of colorectal cancer and liver metastases within six months was considered synchronous. Cost analysis was performed from the perspective of a third-party payer. Median costs with range were estimated using the log-normal distribution of cost using t -test with a one-year time horizon. Results: Among patients undergoing staged resection (n = 678), the estimated median cost was $54, 321 CAD (IQR 45, 472 to 68, 475) and $41, 286 CAD (IQR 31, 633 to 58, 958) for those undergoing simultaneous resection (n = 390), median difference: $13, 035 CAD (p < 0.001). Primary cost driver were all costs related to hospitalization for liver and colon resection, which was higher for the staged approach, median difference: $16, 346 CAD (p < 0.001). This was mainly due to a longer median length of hospital stay in the staged vs. simultaneous group (11 vs. 8 days, p < 0.001 respectively), which was not attributable to differences in major postoperative complication rates (23% vs. 28%, p = 0.067 respectively). Other costs, including cost of chemotherapy within six months of surgery ($11, 681 CAD vs. $8644 CAD, p = 0.074 respectively) and 90-day re-hospitalization cost ($2155 CAD vs. $2931 CAD, p = 0.454 respectively) were similar between groups. Conclusion: Cost of staged resection of synchronous colorectal cancer liver metastases is significantly higher compared to the simultaneous approach, mostly driven by a longer length of hospital stay despite similar postoperative complication rates. Highlights: Colorectal cancer presents with liver metastases at diagnosis in up to 20% of patients. Colon and liver resection can be performed simultaneously, or staged, requiring two anaesthetics. A simultaneous approach led to lower cost considering surgery, readmissions and adjuvant therapy. Decreased cost is primarily driven by shorter cumulative time in hospital with a single operation.